The Association of miR-let 7b and miR-548 with PTEN in Prostate Cancer - Saffari, Mojtaba; Ghaderian, Sayyed Mohammad Hossein; Omrani, Mir Davood; Afsharpad, Mandana; Shankaie, Kimia; Samadaian, Niusha (Urology Journal, 2019)
Purpose: This study aims to investigate the expression level of mir-let7b-3p and mir-548, which are involved in PTEN expression in tissue samples of prostate cancer patients versus benign prostate hyperplasia (BPH) and normal adjacent tissue. Materials and Methods: Prostate cancer tissues were obtained from patients after receiving informed consent. Total RNA extraction and cDNA synthesis were performed for determining gene expression. Results: Ten patients were determined to have high Gleason scores (> 7), 36 and seven samples had intermediate Gleason scores (7?) and BPH, respectively, and 40 samples were derived from normal adjacent tissue. Downregulation of mir-let7b and upregulation of mir-548 expression significantly correlated with high-risk Gleason scores. Conclusion: The present study showed that miR-let7b and/or mir-548 can be considered as potential targets in prostate cancer therapy.